2021
DOI: 10.1101/2021.04.12.439532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-Trait Machine and Deep Learning Models for Genomic Selection using Spectral Information in a Wheat Breeding Program

Abstract: Prediction of breeding values and phenotypes is central to plant breeding and has been revolutionized by the adoption of genomic selection (GS). Use of machine and deep learning algorithms applied to complex traits in plants can improve prediction accuracies in the context of GS. Spectral reflectance indices further provide information about various physiological parameters previously undetectable in plants. This research explores the potential of multi-trait (MT) machine and deep learning models for predictin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Due to the unbalanced nature of the dataset, adjusted means were calculated using residuals obtained using the lme4 R package for within environment analysis. The model equation is represented as Y ij = Block i + Check j + e ij (1) where Y ij is the raw phenotype; Check j is the effect of replicated check cultivar; Block i corresponds to the fixed block effect; and e ij is the residuals [30,31]. Block was considered fixed, as we want to remove that component of variation before exploring the genetic variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the unbalanced nature of the dataset, adjusted means were calculated using residuals obtained using the lme4 R package for within environment analysis. The model equation is represented as Y ij = Block i + Check j + e ij (1) where Y ij is the raw phenotype; Check j is the effect of replicated check cultivar; Block i corresponds to the fixed block effect; and e ij is the residuals [30,31]. Block was considered fixed, as we want to remove that component of variation before exploring the genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Regularization, dropout, and early stopping were applied to control overfitting. Furthermore, information about hyperparameter optimization and deep learning models is referred to in [21,31].…”
Section: Multilayer Perceptron (Mlp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Models trained on 2014 GPC data were used for predictions in 2015 and 2016. Similarly, the 2015 GPC training model was used for 2016 predictions (Sandhu et al 2021c).…”
Section: Genomic Selectionmentioning
confidence: 99%
“…The use of VIs and canopy temperature as predictors were shown to increase model accuracy of genomic and hybrid model accuracies for wheat grain yield 65 . Sandhu et al 66 suggested using spectral information as a secondary trait in genomic prediction provided better prediction accuracy for grain protein content. Galán et al 67 argue that genomic models incorporate genetic relationships between untested candidates and those with known genotypic and phenotypic information, and their study revealed hyperspectral reflectance-derived (HBLUP) relationship matrices (i.e., HTP data) were less prone to genetic relatedness and trait heritability, whereas more highly heritable traits were better predicted by genomic (GBLUP) relationship matrices.…”
Section: Discussionmentioning
confidence: 99%